Cloning of the cDNA for the putative calcium-sensing receptor and its tissue distribution in sea bream (Sparus aurata) - Flanagan, J. A. (2014)
The cDNA for the calcium-sensing receptor (CaSR) gene has been cloned from the marine teleost Sparus aurata, the sea bream. The isolated clones were 3.3 kb long with an open reading frame of 2820 bp, a 50 UTR of 240 bp, and 30 UTR of 248 bp. The gene codes for a mature peptide of 940 amino acids which has three principal domains; the extracellular region is more than half the total protein, there is a seven-transmembrane domain, and there is a short intracellular domain. There is considerable sequence identity, 91%, shared between the CaSR of sea bream and puffer fish but overall similarities with mammalian CaSR peptides vary between 44% for rat and mouse and 48% with human CaSR. Nevertheless, the 18 cysteine residues of the extracellular domain are present in all sequences so far analysed of which 9 form a cysteine-rich region in sea bream similar to mammalian CaSR. The distribution of CaSR in sea bream tissues detected by in situ hybridisation showed gene expression in epithelia associated with ion transport or ion regulation including the hind gut, chloride cells of the gills, operculum, gall bladder, pituitary adenohypophysis, and coronet cells of the saccus vasculosus; this distribution was confirmed by RT-PCR. By in situ hybridisation, CaSR gene expression was also present in olfactory nerves and leucocytes.